Laminate and packaging bag

The laminate structure, featuring a polypropylene stretched substrate, inorganic oxide layer, and a random copolymer-based second surface resin layer, addresses the challenges of recyclability and impact resistance in packaging bags, ensuring effective performance and recyclability after retort treatment.

JP2025058861AActive Publication Date: 2025-04-09DAI NIPPON PRINTING CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024071607
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-04-09
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

Conventional packaging bags made from different resin materials are difficult to recycle due to separation challenges, and laminates made of polypropylene do not adequately meet the impact resistance requirements after retort treatment.

Method used

A laminate structure comprising a barrier substrate with a polypropylene stretched substrate and an inorganic oxide layer, a multi-layer structure with a first and second surface resin layer, and an adhesive and sealant layer, where the second surface resin layer contains a random copolymer of propylene and an α-olefin, ensuring excellent interlayer adhesion and impact resistance.

Benefits of technology

The laminate provides excellent impact resistance and recyclability, maintaining adhesion between layers even after retort treatment, and ensuring the packaging bag remains functional and recyclable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058861000001_ABST
    Figure 2025058861000001_ABST
Patent Text Reader

Abstract

To provide a laminate which is excellent in impact resistance after retort treatment, when being used in a packaging bag such as a retort pouch.SOLUTION: A laminate has a base material, an adhesive layer and a sealant layer in this order in a thickness direction, wherein the base material is a barrier base material having a stretched base material containing polypropylene as a main component and an inorganic oxide layer in this order in a thickness direction, the stretched base material has a multilayer structure having a first surface resin layer, a polypropylene layer and a second surface resin layer in this order in a thickness direction, the first surface resin layer faces the inorganic oxide layer, the second surface resin layer is arranged so as to face the adhesive layer, the second surface resin layer contains 50 mass% or more of a random copolymer of propylene and α-olefin other than the propylene with respect to the total amount of the second surface resin layer, the adhesive layer has thickness of 1 μm or more and 4.5 μm or less and elastic modulus of 20 MPa or more and 50 MPa or less, and the sealant layer contains polypropylene as a main component and has composite elastic modulus of 900 MPa or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a packaging bag. [Background technology]

[0002] Conventionally, packaging bags have been made of a laminate using a polyester film with excellent strength and heat resistance or a nylon film with excellent impact resistance as a substrate and a polyolefin film with excellent heat sealability as a sealant film. However, with the growing demand for the creation of a recycling-oriented society in recent years, packaging bags with high recyclability are in demand, but it was difficult to separate the conventional packaging bags made of different resin materials into individual resin materials.

[0003] Therefore, from the viewpoint of using a single material (mono-material) that is easy to recycle, the use of a single material made of polypropylene has been studied (for example, Patent Document 1). Patent Document 1 discloses a laminate for use as a packaging material for packaging bags, in which a stretched substrate containing polypropylene is used as the substrate instead of a polyester film or a nylon film, and the substrate is combined with a sealant film containing polypropylene. With this laminate, both the substrate and the sealant film are made of polypropylene, improving recyclability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-020391 Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, when a laminate is used to make a packaging bag such as a retort pouch, the laminate is required to have drop impact resistance (impact resistance) to withstand the impact of the pouch being dropped after heat sterilization (retort treatment). However, the reality is that there has been insufficient consideration given to satisfying these required properties for a laminate made of a single material such as polypropylene.

[0006] One of the problems to be solved by the present disclosure is to provide a laminate that has excellent impact resistance after retort treatment when used in a packaging bag such as a retort pouch. [Means for solving the problem]

[0007] The laminate of the present disclosure is a laminate comprising a substrate, an adhesive layer, and a sealant layer in this order in the thickness direction, wherein the substrate is a barrier substrate comprising, in this order in the thickness direction, a stretched substrate containing polypropylene as a main component, and an inorganic oxide layer, the stretched substrate has a multilayer structure comprising, in this order in the thickness direction, a first surface resin layer, a polypropylene layer, and a second surface resin layer, the first surface resin layer is disposed opposite the inorganic oxide layer, and the second surface resin layer is disposed opposite the adhesive layer, the second surface resin layer comprises 50 mass% or more of a random copolymer of propylene and an α-olefin other than propylene, relative to the total amount of the second surface resin layer, the adhesive layer has a thickness of 1 μm or more and 4.5 μm or less and an elastic modulus of 20 MPa or more and 50 MPa or less, and the sealant layer contains polypropylene as a main component and has a composite elastic modulus of 900 MPa or less. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide a laminate that has excellent impact resistance after retort treatment when used in a packaging bag such as a retort pouch. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a laminate. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of a laminate. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 4] FIG. 4 is a schematic cross-sectional view showing one embodiment of a laminate. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 6] FIG. 6 is a schematic cross-sectional view showing one embodiment of a laminate. [Figure 7] FIG. 7 is a front view showing one embodiment of a packaging bag. [Figure 8] FIG. 8 is a front view showing one embodiment of a packaging bag. [Figure 9] FIG. 9 is a schematic diagram showing a method for measuring laminate strength. [Figure 10] FIG. 10 is a diagram showing the measurement results of laminate strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In this specification, when multiple upper limit candidates and multiple lower limit candidates are given for a certain parameter, the numerical range of the parameter may be configured by combining any one of the upper limit candidates and any one of the lower limit candidates. As an example, the description "parameter B is preferably A1 or more, more preferably A2 or more, even more preferably A3 or more, and also preferably A4 or less, more preferably A5 or less, and even more preferably A6 or less." will be explained. In this example, the numerical range of parameter B may be A1 or more and A4 or less, A1 or more and A5 or less, A1 or more and A6 or less, A2 or more and A4 or less, A2 or more and A5 or less, A2 or more and A6 or less, A3 or more and A4 or less, A3 or more and A5 or less, or A3 or more and A6 or less.

[0011] Hereinafter, the embodiments of the present disclosure will be described in detail. The present disclosure can be implemented in many different forms, and is not to be interpreted as being limited to the description of the embodiments exemplified below. In the drawings, the width, thickness, shape, etc. of each layer may be shown diagrammatically compared to the embodiments in order to make the explanation clearer, but these are merely examples and do not limit the interpretation of the present disclosure. In this specification and each figure, elements similar to those already explained with respect to the previous figures may be given the same reference numerals, and detailed explanations may be omitted as appropriate.

[0012] In this specification, the "main component" of a layer or substrate refers to a component whose content in the layer or substrate is more than 50% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0013] In the following description, each of the components (for example, polypropylene, α-olefin, resin material, additive, gas barrier resin, adhesive resin, inorganic oxide) may be used either alone or in combination of two or more.

[0014] [Laminate] The laminate of the present disclosure includes a substrate, an adhesive layer, and a sealant layer in this order in the thickness direction (hereinafter, also simply referred to as "in this order"). The substrate is a barrier substrate having, in the thickness direction, a stretched substrate containing polypropylene as a main component and an inorganic oxide layer in this order. The stretched substrate containing polypropylene as a main component has a multilayer structure including a first surface resin layer, a polypropylene layer, and a second surface resin layer in this order in the thickness direction. The sealant layer contains polypropylene as a main component.

[0015] The laminate of the present disclosure may include two or more substrates. The laminate of the present disclosure may include two or more adhesive layers. The laminate of the present disclosure preferably comprises, in this order, a first substrate, a first adhesive layer, a second substrate, a second adhesive layer, and a sealant layer.

[0016] The first substrate comprises an oriented substrate containing polypropylene as a major component. The second substrate is a barrier substrate having, in the thickness direction, a stretched substrate containing polypropylene as a main component and an inorganic oxide layer in this order. The stretched substrate of the second substrate has a multilayer structure including a first surface resin layer, a polypropylene layer, and a second surface resin layer in this order in the thickness direction. In the following description, the stretched substrate containing polypropylene as a main component is also referred to as "stretched polypropylene substrate."

[0017] In one embodiment of the laminate of the present disclosure, the first substrate is an oriented polypropylene substrate, and the second substrate is a barrier substrate, i.e., the laminate includes, in this order, an oriented polypropylene substrate, an optional printing layer, a first adhesive layer, a barrier substrate, a second adhesive layer, and a sealant layer.

[0018] In this embodiment, the barrier substrate is preferably arranged so that the inorganic oxide layer faces the first adhesive layer and the stretched polypropylene substrate faces the second adhesive layer. With such an arrangement, the second surface resin layer and the second adhesive layer constituting the stretched polypropylene substrate of the second substrate (barrier substrate) are firmly bonded to each other, so that the adhesive strength between the barrier substrate and the sealant layer can be improved. In this embodiment, the laminate exhibits excellent interlayer adhesion. The packaging bag produced using the laminate of this embodiment exhibits excellent drop impact resistance (impact resistance) and hand tearability (openability) even after heat treatment such as retort treatment and boiling treatment.

[0019] 1 to 6 are schematic cross-sectional views showing an embodiment of a laminate according to the present disclosure. The laminate 1 shown in FIGS. 1 to 3 shows an example of a two-layer structure. 1 comprises, in this order, a barrier substrate 20 as a substrate, an adhesive layer 40, and a sealant layer 30. The barrier substrate 20 comprises an oriented polypropylene substrate 22 and an inorganic oxide layer 24. In this example, the inorganic oxide layer 24 is located as the outermost layer of the laminate 1, and constitutes the outermost layer, and the oriented polypropylene substrate 22 is in contact with the adhesive layer 40. The stretched polypropylene substrate 22 has a multilayer structure including, in this order, a first surface layer 22b, a polypropylene layer 22a, and a second surface layer 22c. In this example, the first surface layer 22b contacts the inorganic oxide layer 24, and the second surface layer 22c contacts the adhesive layer 40.

[0020] 2 is similar to FIG 1, except that the barrier substrate 20 includes a surface coating layer 23 between a stretched polypropylene substrate 22 and an inorganic oxide layer 24. In this example, the first surface layer 22b contacts the surface coating layer 23, and the second surface layer 22c contacts the adhesive layer 40. FIG. 3 is the same as FIG. 2, except that the barrier substrate 20 includes an oriented polypropylene substrate 22, a surface coating layer 23, an inorganic oxide layer 24, and a coating layer 25, in this order.

[0021] The laminate 1 shown in FIGS. 4 to 6 shows an example of a three-layer structure. 4 includes, in this order, a stretched polypropylene substrate 10 as a first substrate, a first adhesive layer 40A, a barrier substrate 20 as a second substrate, a second adhesive layer 40B, and a sealant layer 30. The barrier substrate 20 includes a stretched polypropylene substrate 22 and an inorganic oxide layer 24. In this example, the barrier substrate 20 is disposed such that the stretched polypropylene substrate 22 faces the second adhesive layer 40B and the inorganic oxide layer 24 faces the first adhesive layer 40A. The stretched polypropylene substrate 22 has a multilayer structure including, in this order, a first surface layer 22b, a polypropylene layer 22a, and a second surface layer 22c. In this example, the first surface layer 22b contacts the inorganic oxide layer 24, and the second surface layer 22c contacts the second adhesive layer 40B.

[0022] Figure 5 is similar to Figure 4, except that the barrier substrate 20 has a surface coating layer 23 between the stretched polypropylene substrate 22 and the inorganic oxide layer 24. In this example, the first surface layer 22b contacts the surface coating layer 23, and the second surface layer 22c contacts the second adhesive layer 40B. FIG. 6 is similar to FIG. 5, except that the barrier substrate 20 includes an oriented polypropylene substrate 22, a surface coating layer 23, an inorganic oxide layer 24, and a coating layer 25 in this order.

[0023] The polypropylene content ratio (hereinafter also referred to as "mono-material ratio") relative to the total amount of resin material contained in the laminate of the present disclosure is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 88% by mass or more, and particularly preferably 90% by mass or more. A packaging bag produced using such a laminate has, for example, excellent recyclability. The upper limit of the polypropylene content ratio relative to the total amount of resin material contained in the laminate of the present disclosure is not particularly limited, and may be, for example, 99% by mass, 98% by mass, 97% by mass, 96% by mass, 95% by mass, or 94% by mass.

[0024] In this disclosure, the mono-material ratio refers to the ratio of a single polypropylene-based material to the total mass of the resin materials contained in the laminate. However, when a layer contains polypropylene as the main component (i.e., more than 50 mass%), the mono-material ratio is calculated assuming that polypropylene constitutes 100 mass% of the layer.

[0025] <Barrier substrate> The barrier substrate comprises a stretched polypropylene substrate and an inorganic oxide layer. The barrier substrate comprises, for example, a stretched polypropylene substrate and an inorganic oxide layer provided on one surface of the stretched substrate. The barrier substrate may comprise a surface coating layer between the stretched polypropylene substrate and the inorganic oxide layer. The barrier substrate may comprise a coating layer on the inorganic oxide layer. The barrier substrate may have transparency.

[0026] (Polypropylene oriented base material) An example of the stretched polypropylene substrate that the barrier substrate comprises is a multi-layered polypropylene substrate comprising, in this order, a first surface resin layer, an optional adhesive resin layer, a polypropylene layer, an optional adhesive resin layer, and a second surface resin layer. In this embodiment, the barrier substrate comprises a stretched polypropylene substrate and an inorganic oxide layer provided on the surface resin layer of the stretched polypropylene substrate. In this embodiment, the barrier substrate comprises, in this order, a second surface resin layer, an optional adhesive resin layer, a polypropylene layer, an optional adhesive resin layer, a first surface resin layer, and an inorganic oxide layer.

[0027] "Polypropylene layer" In the oriented polypropylene substrate, the polypropylene layer contains polypropylene as a main component. The polypropylene may be any of a homopolymer, a random copolymer, and a block copolymer, and may be a mixture of two or more selected from these. As the polypropylene, biomass-derived polypropylene and / or recycled polypropylene may be used. A propylene homopolymer is a polymer of only propylene. A propylene random copolymer is a random copolymer of propylene and an α-olefin other than propylene. A propylene block copolymer is a copolymer having a polymer block of propylene and a polymer block of at least an α-olefin other than propylene. The polymer block of at least an α-olefin other than propylene may be a polymer block of propylene and an α-olefin other than propylene.

[0028] Examples of the α-olefin include α-olefins having 2 to 20 carbon atoms other than propylene, specifically, ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene.

[0029] Among polypropylenes, random copolymers are preferred from the viewpoint of transparency, homopolymers are preferred when the rigidity and heat resistance of the packaging bag are important, and block copolymers are preferred when the impact resistance of the packaging bag is important. In the present disclosure, among these polypropylenes, homopolymers and block copolymers are more preferred from the viewpoints of heat resistance, impact resistance, and ease of opening, and homopolymers (propylene homopolymers) are even more preferred.

[0030] From the viewpoint of film-forming property and processability, the melt flow rate (MFR) of polypropylene is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and also preferably 50 g / 10 min or less, more preferably 30 g / 10 min or less, for example, 0.1 g / 10 min or more and 50 g / 10 min or less. The MFR of polypropylene is measured in accordance with JIS K7210-1:2014, Method A, under conditions of a temperature of 230° C. and a load of 2.16 kg.

[0031] The polypropylene content in the polypropylene layer is preferably greater than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 85% by mass or more, 90% by mass or more, or 95% by mass or more.

[0032] The polypropylene layer may contain a resin material other than polypropylene, such as, for example, a polyolefin other than polypropylene, such as polyethylene, an acrylic resin, a vinyl resin, a cellulose resin, a polyamide, a polyester, or an ionomer resin. The polypropylene layer may contain additives, such as crosslinkers, antioxidants, antiblocking agents, lubricants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0033] The polypropylene layer may have a single-layer structure or a multi-layer structure. The thickness of the polypropylene layer is preferably 10 μm or more, more preferably 15 μm or more, and also preferably 100 μm or less, more preferably 50 μm or less, for example, 10 μm or more and 100 μm or less. A laminate having a stretched base material including a polypropylene layer having a thickness equal to or greater than the lower limit has, for example, excellent strength and heat resistance. A laminate having a stretched base material including a polypropylene layer having a thickness equal to or less than the upper limit has, for example, excellent processability.

[0034] In this specification, the thickness of the substrate and each layer is measured as follows. A block is prepared by embedding the laminate in an embedding resin, and the block is cut using a commercially available rotary microtome at room temperature (25°C) to prepare a cross section of the laminate. The cross section is obtained by cutting the laminate in the thickness direction perpendicular to the main surface. Finishing is performed with a diamond knife. The thickness of the substrate and each layer is the arithmetic average value of the thicknesses at five points measured by observing the cross section using a scanning electron microscope (SEM, Hitachi, Ltd., SU8000).

[0035] "Second surface resin layer" The second surface resin layer is located between the adhesive layer on the sealant layer or the second adhesive layer and the polypropylene layer. The second surface resin layer contains a random copolymer of propylene and an α-olefin other than propylene. By providing the second surface resin layer containing the random copolymer between the polypropylene layer and the adhesive layer or the second adhesive layer, the adhesive strength between the sealant layer and the stretched polypropylene substrate (i.e., the barrier substrate) can be improved, and the impact resistance of the laminate can also be improved.

[0036] Examples of the random copolymer include a propylene-ethylene random copolymer and a propylene-ethylene-butene random copolymer. Of these, any one or a mixture of two or more can be used as the random copolymer.

[0037] In the propylene-ethylene random copolymer, the content of the ethylene-derived structural unit is preferably 2% by mass or more, more preferably 4% by mass or more. The content is preferably 50% by mass or less, more preferably 40% by mass or less. By being within the above preferred range, for example, the drop impact resistance can be further improved. In the present disclosure, the content of the structural unit can be measured, for example, by a temperature gradient method (TGIC: Thermal Gradient Interaction Chromatography).

[0038] In the propylene-ethylene-butene random copolymer, the content of ethylene-derived structural units and butene-derived structural units is preferably 2% by mass or more, more preferably 4% by mass or more. The content is preferably 50% by mass or less, more preferably 40% by mass or less.

[0039] The content of the random copolymer in the second surface resin layer is 50% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, based on the total amount of the second surface resin layer. By containing 50% by mass or more of the random copolymer, the second surface resin layer exhibits sufficient adhesion strength.

[0040] The second surface resin layer may contain the polypropylene other than the random copolymer or the resin material. The second surface resin layer may contain the above-mentioned additives. The second surface resin layer may be subjected to the above-mentioned surface treatment.

[0041] The ratio of the thickness of the second surface resin layer to the total thickness of the stretched polypropylene substrate is preferably 1% or more, more preferably 1.5% or more, and also preferably 20% or less, more preferably 10% or less, for example 1% or more and 20% or less. The thickness of the second surface resin layer is preferably 0.2 μm or more, more preferably 0.3 μm or more, and also preferably 4 μm or less, more preferably 2 μm or less, for example 0.2 μm or more and 4 μm or less. When the ratio or thickness is equal to or greater than the lower limit, for example, the adhesion with the adhesive layer (second adhesive layer) can be improved, and the laminate strength of the laminate can be improved. When the ratio or thickness is equal to or less than the upper limit, for example, the film formability and processability of the stretched polypropylene substrate and the recyclability of the laminate can be improved.

[0042] "First surface resin layer" The first surface resin layer is located between the inorganic oxide layer and the polypropylene layer. In one embodiment, the first surface resin layer may have the same configuration as the second surface resin layer.

[0043] In one embodiment, the first surface resin layer contains a resin material having a melting point of 180° C. or higher (hereinafter also referred to as a “high melting point resin material”). By providing the first surface resin layer containing a high melting point resin material between the polypropylene layer and the inorganic oxide layer, for example, it is possible to improve the adhesion of the inorganic oxide layer formed on the first surface resin layer and also improve the gas barrier property.

[0044] The melting point of the high melting point resin material is preferably 185°C or higher, more preferably 190°C or higher, and even more preferably 205°C or higher. When the melting point is equal to or higher than the lower limit, for example, the adhesion of the inorganic oxide layer can be improved, the gas barrier property can be improved, and the laminate strength of the laminate can be improved. The melting point of the high melting point resin material is preferably 265°C or lower, more preferably 260°C or lower, and even more preferably 250°C or lower. This can improve, for example, the film formability of the stretched polypropylene substrate.

[0045] In this specification, the melting point of the high melting point resin material and the like is measured in accordance with JIS K7121:2012 (Method of measuring transition temperature of plastics). Specifically, a differential scanning calorimetry (DSC) device is used to measure a DSC curve at a heating rate of 10°C / min, and the melting peak temperature is determined as the melting point.

[0046] The high melting point resin material preferably has a polar group. The polar group refers to a group containing one or more heteroatoms, and examples thereof include ester groups, epoxy groups, hydroxyl groups, amino groups, amide groups, urethane groups, carboxy groups, carbonyl groups, carboxylic anhydride groups, sulfo groups, thiol groups, and halogen groups. Among these, hydroxyl groups, ester groups, amino groups, amide groups, carboxy groups, and carbonyl groups are preferred, and amide groups are more preferred.

[0047] The high melting point resin material may have a melting point of 180° C. or higher, and examples of such materials include polyolefins, vinyl resins, acrylic resins, polyamides, polyimides, polyesters, cellulose resins, and ionomer resins. For example, resin materials having a melting point of 180° C. or higher and having a polar group are preferred, and ethylene-vinyl alcohol copolymers, polyvinyl alcohol, polyesters, and polyamides such as nylon 6, nylon 6,6, and aromatic-containing nylons are more preferred.

[0048] The content of the high melting point resin material in the first surface resin layer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.

[0049] The first surface resin layer may contain the above-mentioned resin materials other than the high melting point resin material. The first surface resin layer may contain the above-mentioned additives. The first surface resin layer may be subjected to the above-mentioned surface treatment.

[0050] The ratio of the thickness of the first surface resin layer to the total thickness of the stretched polypropylene substrate is preferably 1% or more, more preferably 1.5% or more, and also preferably 10% or less, more preferably 5% or less, for example 1% or more and 10% or less. The thickness of the first surface resin layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and also preferably 5 μm or less, more preferably 4 μm or less, for example 0.1 μm or more and 5 μm or less. When the ratio or thickness is equal to or greater than the lower limit, for example, the adhesion of the inorganic oxide layer can be improved, the gas barrier property can be improved, and the laminate strength of the laminate can be improved. When the ratio or thickness is equal to or less than the upper limit, for example, the film formability and processability of the stretched polypropylene substrate and the recyclability of the laminate can be improved.

[0051] "Adhesive resin layer" The stretched polypropylene substrate may have an adhesive resin layer between the polypropylene layer and either or both of the first and second surface resin layers. This can improve the adhesion between these layers. The thickness of the adhesive resin layer is, for example, 1 μm or more and 15 μm or less. The adhesive resin layer can be formed, for example, from an adhesive resin. Examples of the adhesive resin include polyether, polyester, polyurethane, silicone resin, epoxy resin, vinyl resin, phenolic resin, polyolefin, and acid-modified polyolefin. Among these, polyolefin and its acid-modified polyolefin are preferred from the viewpoint of recyclability of the laminate, and polypropylene and its acid-modified polyolefin are more preferred.

[0052] In one embodiment, the stretched polypropylene substrate is a coextruded stretched resin film. The coextruded stretched resin film can be produced, for example, by forming a laminated film using a T-die method or an inflation method, and then stretching the laminated film.

[0053] The stretching treatment for the polypropylene substrate may be uniaxial stretching or biaxial stretching. The stretching ratio in the MD direction is preferably 2 times or more, more preferably 5 times or more, and preferably 15 times or less, more preferably 13 times or less. The stretching ratio in the TD direction is preferably 2 times or more, more preferably 5 times or more, and preferably 15 times or less, more preferably 13 times or less. By setting the stretching ratio at 2 times or more, the strength and heat resistance of the substrate can be improved. From the viewpoint of the breaking limit of the substrate, the stretching ratio is preferably 15 times or less. The oriented polypropylene substrate is, for example, a biaxially oriented substrate.

[0054] The thickness of the stretched polypropylene substrate is preferably 10 μm or more, more preferably 15 μm or more, and also preferably 100 μm or less, more preferably 50 μm or less, for example, 10 μm or more and 100 μm or less. A laminate having a stretched substrate with a thickness equal to or greater than the lower limit has, for example, excellent strength and heat resistance. A laminate having a stretched substrate with a thickness equal to or less than the upper limit has, for example, excellent processability.

[0055] (Surface coating layer) The barrier substrate may include a surface coating layer containing a resin material having a polar group between the stretched polypropylene substrate (the first surface resin layer constituting the stretched polypropylene substrate) and the inorganic oxide layer. Such a barrier substrate has excellent adhesion to the inorganic oxide layer and also has excellent gas barrier properties. Such a barrier substrate includes, in this order, the stretched polypropylene substrate, the surface coating layer, and the inorganic oxide layer.

[0056] The polar group refers to a group containing one or more heteroatoms, and examples thereof include ester group, epoxy group, hydroxyl group, amino group, amide group, urethane group, carboxyl group, carbonyl group, carboxylic anhydride group, sulfo group, thiol group, and halogen group. Among these, carboxyl group, carbonyl group, ester group, hydroxyl group, amino group, amide group, and urethane group are preferred, and carboxyl group, hydroxyl group, amide group, and urethane group are more preferred.

[0057] Examples of resin materials having polar groups include ethylene-vinyl alcohol copolymers (EVOH), polyvinyl alcohol (PVA), polyester, polyethyleneimine, hydroxyl-containing acrylic resins, polyamides such as nylon 6, nylon 6,6, aromatic-containing nylon, and amorphous nylon, and polyurethane. Among these, ethylene-vinyl alcohol copolymers, polyvinyl alcohol, hydroxyl-containing acrylic resins, polyamides, and polyurethanes are more preferred.

[0058] The surface coating layer can be formed, for example, using a water-based emulsion or a solvent-based emulsion. Examples of the water-based emulsion include a polyamide-based emulsion, a polyethylene-based emulsion, and a polyurethane-based emulsion. Examples of the solvent-based emulsion include an acrylic resin-based emulsion and a polyester-based emulsion.

[0059] The content of the resin material having a polar group in the surface coat layer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. The surface coating layer may contain the above-mentioned resin materials other than the resin material having a polar group. The surface coating layer may contain the above-mentioned additives.

[0060] The ratio of the thickness of the surface coat layer to the total thickness of the polypropylene stretched substrate and the surface coat layer is preferably 0.08% or more, more preferably 0.2% or more, even more preferably 1% or more, and also preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, even more preferably 5% or less, for example, 0.08% or more and 20% or less. The thickness of the surface coat layer is preferably 0.02 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, even more preferably 0.2 μm or more, and also preferably 10 μm or less, more preferably 5 μm or less, for example, 0.02 μm or more and 10 μm or less. When the ratio or thickness is the lower limit or more, for example, the adhesion of the inorganic oxide layer can be improved, the gas barrier property can be improved, and the laminate strength of the laminate can be improved. When the ratio or thickness is the upper limit or less, for example, the processability of the barrier substrate and the recyclability of the laminate can be improved.

[0061] For example, polypropylene or a resin composition containing polypropylene is formed into a film using a T-die method, an inflation method, or the like to obtain a polypropylene substrate, and then the substrate is stretched. A coating liquid for forming a surface coating layer is applied to the obtained stretched substrate, and the substrate is dried, thereby producing a resin substrate having a polypropylene stretched substrate and a surface coating layer.

[0062] (Inorganic oxide layer) The barrier substrate comprises an inorganic oxide layer. The inorganic oxide layer contains one or more inorganic oxides, for example, a vapor-deposited film of an inorganic oxide. A laminate comprising the barrier substrate has excellent gas barrier properties, specifically, oxygen barrier properties and water vapor barrier properties. A packaging bag produced using such a laminate can suppress oxidation deterioration of the contents filled in the packaging bag, and suppress the mass loss of the contents. The barrier substrate may, for example, comprise an inorganic oxide layer on the surface coat layer, or may comprise an inorganic oxide layer on the first surface resin layer.

[0063] Examples of inorganic oxides include aluminum oxide (alumina), silicon oxide (silica), magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, barium oxide, and silicon carbide oxide (carbon-containing silicon oxide). Among these, silica, silicon carbide oxide, and alumina are preferred.

[0064] In one embodiment, silica is more preferable as the inorganic oxide since no aging treatment is required after the formation of the inorganic oxide layer.In one embodiment, carbon-containing silicon oxide is more preferable as the inorganic oxide since the deterioration of the gas barrier property can be suppressed even when the laminate is bent.

[0065] The thickness of the inorganic oxide layer is preferably 1 nm or more, more preferably 5 nm or more, even more preferably 10 nm or more, and is preferably 150 nm or less, more preferably 60 nm or less, even more preferably 40 nm or less, for example, 1 nm or more and 150 nm or less. A laminate having an inorganic oxide layer whose thickness is equal to or greater than the lower limit has, for example, excellent oxygen barrier properties and water vapor barrier properties. A laminate having an inorganic oxide layer whose thickness is equal to or less than the upper limit can, for example, suppress the occurrence of cracks in the inorganic oxide layer and has excellent recyclability.

[0066] The surface of the inorganic oxide layer may be subjected to the above-mentioned surface treatment.

[0067] Methods for forming inorganic oxide layers, particularly inorganic oxide vapor deposition films, include, for example, physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, as well as chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.

[0068] The inorganic oxide layer may be a single layer formed by one deposition process, or may be a multilayer formed by multiple deposition processes. When the inorganic oxide layer is a multilayer, each layer may be composed of the same inorganic oxide or different inorganic oxides. Each layer may be formed by the same method or different methods.

[0069] The inorganic oxide layer is preferably a vapor-deposited film formed by a CVD method, and more preferably a carbon-containing silicon oxide vapor-deposited film formed by a CVD method. A laminate including such an inorganic oxide layer has, for example, excellent bending resistance.

[0070] The carbon-containing silicon oxide vapor deposition film contains silicon, oxygen and carbon. In one embodiment of the carbon-containing silicon oxide vapor deposition film, the carbon ratio C is preferably 3% or more, more preferably 5% or more, even more preferably 10% or more, and is preferably 50% or less, more preferably 40% or less, even more preferably 35% or less, for example, 3% or more and 50% or less, relative to 100% of the total of the three elements silicon, oxygen, and carbon. By setting the carbon ratio C in the above range, for example, even if the laminate is bent, the deterioration of the gas barrier property can be suppressed. In this specification, the ratio of each element is on a molar basis.

[0071] In one embodiment of the carbon-containing silicon oxide vapor deposition film, the silicon ratio Si is preferably 1% or more, more preferably 3% or more, even more preferably 8% or more, and is preferably 45% or less, more preferably 38% or less, even more preferably 33% or less, for example 1% or more and 45% or less, relative to the total of the three elements silicon, oxygen and carbon 100%. The oxygen ratio O is preferably 10% or more, more preferably 20% or more, even more preferably 25% or more, and is preferably 70% or less, more preferably 65% ​​or less, even more preferably 60% or less, for example 10% or more and 70% or less, relative to the total of the three elements silicon, oxygen and carbon 100%. By setting the silicon ratio Si and the oxygen ratio O in the above ranges, for example, even if the laminate is bent, the deterioration of the gas barrier property can be further suppressed.

[0072] In one embodiment of the carbon-containing silicon oxide vapor-deposited film, the oxygen ratio O is preferably higher than the carbon ratio C, and the silicon ratio Si is preferably lower than the carbon ratio C. The oxygen ratio O is preferably higher than the silicon ratio Si, that is, the ratios are preferably in the order of O, C, and Si. This makes it possible to further suppress the deterioration of the gas barrier properties even when the laminate is bent, for example.

[0073] The proportions C, Si, and O in the carbon-containing silicon oxide vapor-deposited film are measured by narrow scan analysis using X-ray photoelectron spectroscopy (XPS) under the following measurement conditions.

[0074] (Measurement conditions) Equipment used: "ESCA-3400" (manufactured by Kratos) [1] Spectral collection conditions Incident X-ray: MgKα (non-monochromatic X-ray, hν=1253.6eV) X-ray output: 150W (10kV 15mA) Measurement area: approx. 6mmφ Photoelectron capture angle: 90 degrees [2] Ion sputtering conditions Ion species: Ar+ Ar gas introduction pressure: 2.0×10-2 Pa Acceleration voltage: 0.2 (kV) Emission current: 20 (mA) Ion sputtering time: 30 seconds, spectrum collected

[0075] (covering layer) The barrier substrate may further include a coating layer on the inorganic oxide layer. That is, the barrier substrate may further include a coating layer on the surface of the inorganic oxide layer opposite to the surface facing the stretched polypropylene substrate. A laminate including such a barrier substrate has, for example, excellent oxygen barrier properties and water vapor barrier properties.

[0076] In one embodiment, the coating layer contains a resin component. Examples of the resin component include polyolefins such as polyethylene, polypropylene, polybutene, and polymethylpentene, vinyl resins, acrylic resins, polyesters, urethane resins, melamine resins, and epoxy resins. The content of the resin component in the coating layer is preferably more than 50% by mass, more preferably 75% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, for example, more than 50% by mass and 95% by mass or less. The coating layer may contain the above-mentioned additives.

[0077] The thickness of the coating layer is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 3 μm or less, even more preferably 1 μm or less, for example, 0.01 μm or more and 5 μm or less. Such a coating layer has, for example, excellent scratch resistance.

[0078] The coating layer can be formed, for example, by applying a coating liquid for the coating layer to the surface of the inorganic oxide layer and drying it. The coating liquid for the coating layer can be prepared, for example, by mixing the above-mentioned resin component and, if necessary, an additive and a solvent. Details of these components are as described above. Examples of the coating method for the coating liquid for the coating layer include known coating methods. Examples of the drying method for the applied coating liquid for the coating layer include methods that apply heat, such as hot air drying, hot roll drying, and infrared irradiation. The drying temperature may be 50°C or higher, or 150°C or lower.

[0079] In one embodiment, the coating layer may be a barrier coat layer containing a gas barrier resin. Examples of the gas barrier resin include ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyacrylonitrile, polyester, polyamide such as nylon 6, nylon 6,6 and polymetaxylylene adipamide, polyurethane, and acrylic resin. The content of the gas barrier resin in the barrier coat layer is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. Such a barrier coat layer has, for example, excellent gas barrier properties. The barrier coat layer may contain the above-mentioned additives.

[0080] The thickness of the barrier coat layer containing the gas barrier resin is preferably 0.01 μm or more, more preferably 0.1 μm or more, and also preferably 10 μm or less, more preferably 5 μm or less, for example, 0.01 μm or more and 10 μm or less. A barrier substrate having a barrier coat layer whose thickness is equal to or greater than the lower limit has, for example, excellent gas barrier properties. A barrier substrate having a barrier coat layer whose thickness is equal to or less than the upper limit can improve, for example, the processability and recyclability of the laminate.

[0081] The barrier coat layer can be formed, for example, by dissolving or dispersing a material such as a gas barrier resin in water or an appropriate organic solvent, applying the resulting coating liquid to the surface of the inorganic oxide layer, and drying it. The barrier coat layer can also be formed, for example, by applying a commercially available barrier coating agent and drying it.

[0082] In one embodiment, the coating layer may be a gas barrier coating film formed by polycondensing a composition containing a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, and the like. A barrier substrate having a gas barrier coating film on an inorganic oxide layer has, for example, excellent gas barrier properties. The gas barrier coating film includes a hydrolysis polycondensate obtained by hydrolyzing and polycondensing the metal alkoxide or the like by a sol-gel method. By providing such a gas barrier coating film on an inorganic oxide layer, for example, the occurrence of cracks in the inorganic oxide layer can be effectively suppressed.

[0083] The metal alkoxide is represented, for example, by the formula (1). R 1 n M(OR 2 ) m (1) In formula (1), R 1 and R 2 each independently represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M. 1 and R 2 In the above, examples of the organic group include alkyl groups having 1 to 8 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, t-butyl, n-hexyl, and n-octyl. The metal atom M is, for example, silicon, zirconium, titanium, or aluminum. Examples of the metal alkoxide include alkoxysilanes, such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane.

[0084] Examples of the water-soluble polymer include hydroxyl group-containing polymers such as polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Either polyvinyl alcohol or ethylene-vinyl alcohol copolymer may be used, or both may be used in combination, depending on the desired physical properties such as oxygen barrier property, water vapor barrier property, water resistance, and weather resistance. Also, a gas barrier coating film obtained using polyvinyl alcohol and a gas barrier coating film obtained using ethylene-vinyl alcohol copolymer may be laminated. The amount of the water-soluble polymer used is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and preferably 500 parts by mass or less, based on 100 parts by mass of the metal alkoxide.

[0085] A silane coupling agent may be used together with the metal alkoxide. As the silane coupling agent, a known organoalkoxysilane containing an organic reactive group can be used, and an organoalkoxysilane having an epoxy group is preferable, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned. The amount of the silane coupling agent used is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the metal alkoxide.

[0086] The gas barrier composition may contain water in a ratio of preferably 0.1 mol or more, more preferably 0.5 mol or more, and preferably 100 mol or less, more preferably 60 mol or less, per mol of metal alkoxide. By making the water content equal to or greater than the lower limit, for example, the oxygen barrier property and water vapor barrier property of the laminate can be improved. By making the water content equal to or less than the upper limit, for example, the hydrolysis reaction can be carried out quickly.

[0087] The gas barrier composition may contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butyl alcohol.

[0088] The sol-gel catalyst is preferably an acid or an amine compound. Examples of the acid include mineral acids such as sulfuric acid, hydrochloric acid, and nitric acid; and organic acids such as acetic acid and tartaric acid. The amount of the acid used is preferably 0.001 mol or more and 0.05 mol or less per mol of the total amount of the metal alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent.

[0089] As the amine compound, the tertiary amine that is substantially insoluble in water and soluble in organic solvent is suitable, for example, N,N-dimethylbenzylamine, tripropylamine, tributylamine and tripentylamine can be mentioned.The amount of the amine compound used is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and also preferably 1.0 parts by mass or less, more preferably 0.3 parts by mass or less, based on 100 parts by mass of the total amount of metal alkoxide and silane coupling agent.

[0090] Examples of methods for applying the gas barrier composition include application means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brush coating, bar coating, and applicator coating.

[0091] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. A gas barrier composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and, if necessary, a silane coupling agent. A polycondensation reaction gradually proceeds in the composition. The composition is applied on an inorganic oxide layer by a conventional method and dried. This drying causes further polycondensation of the metal alkoxide and the water-soluble polymer (and the silane coupling agent if the composition contains a silane coupling agent) to form a composite polymer layer. The above operation may be repeated to laminate a plurality of composite polymer layers. For example, the applied composition is heated at a temperature of preferably 20° C. or higher, more preferably 50° C. or higher, and even more preferably 70° C. or higher, and also at a temperature of preferably 150° C. or lower, more preferably 120° C. or lower, and even more preferably 100° C. or lower for 1 second to 10 minutes. This allows the formation of a gas barrier coating film.

[0092] The thickness of the gas barrier coating film is preferably 0.01 μm or more, more preferably 0.1 μm or more, and is preferably 2 μm or less, more preferably 1 μm or less, and even more preferably 0.5 μm or less, for example, 0.01 μm or more and 2 μm or less, which can improve the gas barrier property, suppress the occurrence of cracks in the inorganic oxide layer, and improve the recyclability of the packaging bag.

[0093] <Polypropylene oriented base material> The stretched polypropylene substrate as the first substrate may be any of the stretched polypropylene substrates described in the section "Barrier Substrate." The stretched polypropylene substrate as the first substrate may be any of the stretched substrates in other embodiments. The oriented polypropylene substrate of the first substrate and the oriented polypropylene substrate of the second substrate may be the same or different.

[0094] (Another embodiment of stretched substrate) The stretched substrate in another embodiment contains polypropylene as a main component. The details of polypropylene are as described above, and therefore will not be described in this section.

[0095] In other embodiments, the polypropylene content in the stretched substrate is preferably greater than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 85% by mass or more, 90% by mass or more, or 95% by mass or more.

[0096] In another embodiment, the stretched substrate may contain the above-mentioned resin material other than polypropylene. The stretched substrate in another embodiment may contain the additives described above.

[0097] The stretched substrate of another embodiment is a polypropylene substrate that has been subjected to a stretching treatment. The laminate including the stretched substrate of another embodiment is, for example, excellent in heat resistance, impact resistance, water resistance and dimensional stability, and is suitable as a packaging material for constituting a packaging bag that is subjected to, for example, a retort treatment or a boiling treatment. The stretching process may be uniaxial stretching or biaxial stretching. When stretching in the machine direction (flow direction of the substrate, MD direction), the stretching ratio is preferably 2 times or more, more preferably 5 times or more, and preferably 15 times or less, more preferably 13 times or less. When stretching in the width direction (direction perpendicular to the MD direction, TD direction), the stretching ratio is preferably 2 times or more, more preferably 5 times or more, and preferably 15 times or less, more preferably 13 times or less. By setting the stretching ratio at 2 times or more, the strength and heat resistance of the substrate can be improved, and the printability of the substrate can be improved. From the viewpoint of the breaking limit of the substrate, the stretching ratio is preferably 15 times or less. Another embodiment of the oriented substrate for use as the first substrate is, for example, a biaxially oriented polypropylene substrate.

[0098] The stretched substrate of another embodiment may be surface-treated. This can improve the adhesion between the stretched substrate of another embodiment and other layers, for example. Examples of the surface treatment include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment; and chemical treatments such as oxidation treatment using chemicals. An easy-adhesion layer may be provided on the surface of the stretched substrate in another embodiment.

[0099] The stretched substrate in another embodiment may have a single-layer structure or a multi-layer structure. The thickness of the stretched substrate in another embodiment is preferably 10 μm or more, more preferably 15 μm or more, and also preferably 100 μm or less, more preferably 50 μm or less, for example, 10 μm or more and 100 μm or less. A laminate having a stretched substrate with a thickness equal to or greater than the lower limit has, for example, excellent strength and heat resistance. A laminate having a stretched substrate with a thickness equal to or less than the upper limit has, for example, excellent processability.

[0100] <Print layer> The laminate of the present disclosure may include a printed layer on the surface of a substrate such as a first substrate and a second substrate. The image formed on the printed layer is not particularly limited, and may be a character, a pattern, a symbol, or a combination thereof. The printed layer may be formed using an ink derived from biomass. This can further reduce the environmental load.

[0101] Examples of methods for forming the printed layer include conventionally known printing methods such as gravure printing, offset printing, and flexographic printing. Among these, flexographic printing is preferred from the viewpoint of reducing the environmental load. The thickness of the printed layer is, for example, not less than 0.5 μm and not more than 3 μm.

[0102] <Adhesive layer> In one embodiment, the laminate of the present disclosure comprises an adhesive layer between the substrate and the sealant layer. In one embodiment, the laminate of the present disclosure comprises a first adhesive layer between the first substrate and the second substrate. In one embodiment, the laminate of the present disclosure comprises a second adhesive layer between the second substrate and the sealant layer. Such a laminate has excellent lamination strength, for example, between the substrate / sealant layer, between the first substrate / second substrate, and between the second substrate / sealant layer.

[0103] (First adhesive layer) The elastic modulus of the cross section of the first adhesive layer measured using an atomic force microscope (AFM) is preferably 5 MPa or more, more preferably 10 MPa or more, even more preferably 12 MPa or more, and is preferably 150 MPa or less, more preferably 100 MPa or less, even more preferably 80 MPa or less, for example, 5 MPa or more and 150 MPa or less. A packaging bag produced using a laminate having a first adhesive layer with an elastic modulus within the above range tends to have excellent gas barrier properties and appearance even after heat treatment such as retort treatment. In addition, when a printing layer is provided on the surface of the first base material facing the first adhesive layer, a first adhesive layer with an elastic modulus of the upper limit or less tends to have excellent adhesion to the printing layer.

[0104] Here, the elastic modulus of the adhesive layer is measured on a cross section of the adhesive layer using an atomic force microscope (AFM). Details of the conditions for measuring the elastic modulus by AFM are described in the Examples section.

[0105] The thickness of the first adhesive layer is 1.0 μm or more, preferably 1.5 μm or more, more preferably 2.0 μm or more, even more preferably 2.5 μm or more, and also preferably 10.0 μm or less, more preferably 8.0 μm or less, even more preferably 6.0 μm or less, particularly preferably 5.0 μm or less, for example, 1.0 μm or more and 10.0 μm or less. When a printed layer is provided on the surface of the first substrate facing the first adhesive layer, the first adhesive layer having a thickness of the lower limit or more can well cover the step caused by the printed layer, and tends to be able to obtain a packaging bag with a good appearance. A laminate having a first adhesive layer having a thickness of the lower limit or more tends to have excellent lamination strength even after heat treatment.

[0106] (Second adhesive layer) The elastic modulus measured by AFM on the cross section of the second adhesive layer is 20 MPa or more, preferably 25 MPa or more, more preferably 30 MPa. The elastic modulus is 50 MPa or less, preferably 45 MPa or less, more preferably 40 MPa or less. The elastic modulus of the second adhesive layer is, for example, 20 MPa or more and 50 MPa or less. A laminate having a second adhesive layer with an elastic modulus in the above range tends to have excellent lamination strength and excellent impact resistance. The second adhesive layer having such an elastic modulus can be formed, for example, by using a solvent-free adhesive described later, and by appropriately changing the type and molecular weight of the polymer component contained in the base agent, the type of the curing agent, the molar ratio (NCO / OH), and the aging conditions described later.

[0107] The thickness of the second adhesive layer is 1.0 μm or more, preferably 1.2 μm or more, more preferably 1.4 μm or more. The thickness of the second adhesive layer is 4.5 μm or less, preferably 4.0 μm or less, more preferably 3.5 μm or less. The thickness of the second adhesive layer is 1.0 μm or more and 4.5 μm or less. A laminate having such a second adhesive layer can suppress blocking caused by the adhesive protruding during winding or the occurrence of winding slippage. In addition, a packaging bag produced using a laminate having such a second adhesive layer tends to have excellent impact resistance, therefore resistance to bag breakage due to dropping, and also excellent tearability, therefore ease of opening. In addition, the packaging bag is, for example, excellent in recyclability.

[0108] In the laminate of the present disclosure, the adhesive layer (e.g., an adhesive layer of a two-layer structure and a second adhesive layer of a three-layer structure) located between the sealant layer and the substrate adjacent to the sealant layer has a value obtained by multiplying the elastic modulus (MPa) and the thickness (μm) of the adhesive layer of preferably 35 or more, more preferably 40 or more, and even more preferably 50 or more. The value obtained by multiplying the elastic modulus and the thickness of the adhesive layer is preferably 95 or more, and preferably 80 or less, and more preferably 60 or less. The value obtained by multiplying the elastic modulus and the thickness of the adhesive layer is, for example, 35 or more and 95 or less.

[0109] In one embodiment of the laminate of the present disclosure, an adhesive layer having a value obtained by multiplying the elastic modulus (MPa) and the thickness (μm) of 35 to 95 is located between the sealant layer and the substrate adjacent to the sealant layer. A packaging bag produced using a laminate of this embodiment tends to be superior in impact resistance (bag resistance to drop breakage) and hand tearability (ease of opening) after retort treatment.

[0110] (glue) The adhesive layer, the first adhesive layer, and the second adhesive layer are each composed of an adhesive. The adhesive forming the first adhesive layer and the adhesive forming the second adhesive layer may be the same or different. The adhesive may be any of a one-component curing adhesive, a two-component curing adhesive, and a non-curing adhesive, and a two-component curing adhesive is preferred from the viewpoint of easily adjusting the elastic modulus to the above-mentioned range.

[0111] A method for obtaining a laminate using an adhesive includes a method in which an adhesive is applied to an object, and then another object is placed on the formed adhesive layer, and the adhesive layer sandwiched between the two is allowed to harden. Examples of the object include a first substrate, a second substrate, and a sealant film. The process of allowing the adhesive layer to harden is also referred to as the "aging process" below.

[0112] The aging conditions of the adhesive are described below. The aging temperature is preferably 25°C or higher, more preferably 30°C or higher, and even more preferably 35°C or higher, and is preferably 80°C or lower, more preferably 70°C or lower, and even more preferably 60°C or lower. The aging time is preferably 5 hours or higher, more preferably 10 hours or higher, and even more preferably 20 hours or higher, and is preferably 150 hours or lower, more preferably 135 hours or lower, and even more preferably 120 hours or lower. By increasing the aging temperature, the elastic modulus of the adhesive layer tends to increase. By increasing the aging time, the elastic modulus of the adhesive layer tends to increase.

[0113] Examples of adhesives include polyurethane adhesives, polyester adhesives, polyether adhesives, rubber adhesives, vinyl adhesives, olefin adhesives, silicone adhesives, epoxy adhesives, and phenol adhesives. Among these, from the viewpoint of easily adjusting the elastic modulus to the above-mentioned range, polyurethane adhesives, polyester adhesives, and polyether adhesives are preferred, polyurethane adhesives and polyester adhesives are more preferred, polyurethane adhesives are even more preferred, and two-liquid curing polyurethane adhesives are particularly preferred.

[0114] The adhesive may be a solvent-based adhesive or a solventless adhesive. A solvent-based adhesive is an adhesive used in a method in which the adhesive is applied to an object, heated in an oven or the like to volatilize the solvent in the adhesive, and then the adhesive is bonded to another object. In the case of a two-liquid curing adhesive, either the base agent or the curing agent, or both, contain a solvent. Examples of the solvent include organic solvents, specifically, hydrocarbon solvents such as toluene, xylene, n-hexane, and methylcyclohexane; ester solvents such as ethyl acetate, n-propyl acetate, n-butyl acetate, and isobutyl acetate; alcohol solvents such as methanol, ethanol, isopropyl alcohol, n-butyl alcohol, and isobutyl alcohol; and ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.

[0115] A solvent-free adhesive is an adhesive that is applied to an object and then bonded to another object without necessarily going through a process of heating in an oven or the like to volatilize the solvent. In the case of a two-component curing adhesive, both the base agent and the curing agent are substantially free of solvent. "Substantially free of solvent" includes cases where the solvent used as a reaction medium during the manufacture of the adhesive's components, or the base agent and / or curing agent in the case of a two-component curing adhesive, is not completely removed, leaving trace amounts of solvent remaining in the adhesive, or the base agent and / or curing agent in the case of a two-component curing adhesive.

[0116] The two-component curing polyurethane adhesive has a base agent and a curing agent. The two-component curing polyurethane adhesive may be a solvent-based adhesive or a solventless adhesive. The two-component curing polyurethane adhesive will be described below.

[0117] The polyurethane adhesive has, for example, a base agent containing a polyol compound and a curing agent containing a polyisocyanate compound. Examples of the cured product (reaction product) formed by mixing such a base agent and a curing agent include polyurethane, specifically polyester polyurethane, polyether polyurethane, polycarbonate polyurethane, and acrylic polyurethane.

[0118] The polyol compound has two or more hydroxyl groups in one molecule. Examples of the polyol compound include polyester polyurethane polyol, polyester polyol, polyether polyol, polycarbonate polyol and acrylic polyol. Among these, polyester polyurethane polyol and polyester polyol are preferred from the viewpoint of easily obtaining an adhesive layer having an elastic modulus in the above-mentioned range, and in the case of a solvent-based adhesive, polyester polyurethane polyol is more preferred, and in the case of a solventless adhesive, polyester polyol is more preferred.

[0119] Polyester polyurethane polyol is a compound having two or more hydroxy groups, ester bonds, and urethane bonds in one molecule, and has, for example, a polyester polyurethane structure as the main skeleton. Polyester polyol is a compound having two or more hydroxy groups and ester bonds in one molecule, and has, for example, a polyester structure as the main skeleton. Polyether polyol is a compound having two or more hydroxy groups and ether bonds in one molecule. Polycarbonate polyol is a compound having two or more hydroxy groups and carbonate bonds in one molecule.

[0120] The weight average molecular weight (Mw) of the polymer component (e.g., polyol compound) contained in the base of the two-component curing and solvent-based adhesive is, from the viewpoint of coatability, preferably 11,000 or more, more preferably 13,000 or more, even more preferably 15,000 or more, even more preferably 18,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 50,000 or less, and even more preferably 40,000 or less. The smaller the Mw, the higher the elastic modulus of the adhesive layer tends to be, and the larger the Mw, the lower the elastic modulus of the adhesive layer tends to be. The polydispersity (Mw / Mn) of the polymer component (e.g., polyol compound) contained in the base material is preferably 5.0 or less, more preferably 4.5 or less, and even more preferably 4.0 or less, and is preferably 1.5 or more, more preferably 2.0 or more, and even more preferably 2.5 or more. Here, Mn is the number average molecular weight of the polymer component (e.g., polyol compound) contained in the base material. Each average molecular weight is measured by gel permeation chromatography (GPC) in accordance with JIS K7252-1:2016 and is a value converted into polystyrene.

[0121] From the viewpoint of coatability, the weight average molecular weight (Mw) of the polymer component (e.g., polyol compound) contained in the base agent of the two-component curing solventless adhesive is preferably 800 or more, more preferably 1,200 or more, and even more preferably 2,000 or more, and is preferably 10,000 or less, more preferably 8,000 or less, and even more preferably 6,000 or less. The smaller the Mw, the higher the elastic modulus of the adhesive layer tends to be, and the larger the Mw, the lower the elastic modulus of the adhesive layer tends to be. The polydispersity (Mw / Mn) of the polymer component (e.g., polyol compound) contained in the base agent is preferably 2.8 or less, more preferably 2.7 or less, even more preferably 2.6 or less, particularly preferably 2.5 or less, and is preferably 1.2 or more, more preferably 1.5 or more, and even more preferably 2.0 or more, where Mn is the number average molecular weight of the polymer component (e.g., polyol compound) contained in the base agent.

[0122] The polyisocyanate compound has two or more isocyanate groups in one molecule. Examples of the polyisocyanate compound include aromatic isocyanates and aliphatic isocyanates. The polyisocyanate compound may be a blocked isocyanate compound obtained by addition reaction using a known isocyanate blocking agent by a known and conventional appropriate method.

[0123] Examples of polyisocyanate compounds include aliphatic isocyanate compounds such as tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), norbornene diisocyanate, and isophorone diisocyanate (IPDI); aromatic isocyanate compounds such as diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate (XDI), hydrogenated xylylene diisocyanate, tolylene diisocyanate (TDI), naphthalene diisocyanate, and α,α,α',α'-tetramethyl-m-xylylene diisocyanate, dimers and trimers (e.g., isocyanurate bodies) derived from these compounds; and adducts, biuret bodies, and allophanate bodies obtained by reacting these compounds with low-molecular-weight active hydrogen compounds or their alkylene oxide adducts, or high-molecular-weight active hydrogen compounds.

[0124] Examples of low molecular weight active hydrogen compounds include ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexamethylene glycol, 1,8-octamethylene glycol, 1,4-cyclohexanedimethanol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolethane, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine and metaxylylenediamine, and trimethylolpropane is preferred. Examples of high molecular weight active hydrogen compounds include polyester, polyether polyol and polyamide.

[0125] The base agent containing a polyol compound and the curing agent containing a polyisocyanate compound are preferably used in such an amount ratio that the molar ratio (NCO / OH) between the total isocyanate groups of the polyisocyanate compound and the total hydroxyl groups of the polyol compound is as follows. That is, the molar ratio (NCO / OH) is preferably 0.5 or more, more preferably 1.0 or more, even more preferably 1.5 or more, and is preferably 8.0 or less, more preferably 6.0, even more preferably 5.0 or less, and in the case of a solventless adhesive, it is even more preferably 4.0 or less, particularly preferably 3.0 or less. The larger the molar ratio (NCO / OH), the higher the elastic modulus of the adhesive layer tends to be, and the smaller the molar ratio (NCO / OH), the lower the elastic modulus of the adhesive layer tends to be.

[0126] <Sealant layer> The laminate of the present disclosure includes a sealant layer. The sealant layer contains polypropylene as a main component. The sealant layer contains the same type of resin material as the oriented polypropylene substrate, i.e., polypropylene as a main component. This allows the laminate to be made into a mono-material. In other words, after collecting used packaging bags, there is no need to separate the substrate and the sealant layer, improving the recyclability of the packaging bags. The sealant layer may have a single-layer structure or a multi-layer structure.

[0127] The content of polypropylene in the sealant layer is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, particularly preferably 85% by mass or more, 90% by mass or more, or 95% by mass or more. A laminate having such a sealant layer has, for example, excellent recyclability.

[0128] Examples of polypropylene include propylene homopolymers, propylene random copolymers such as propylene-α-olefin random copolymers, and propylene block copolymers such as propylene-α-olefin block copolymers. Details of the α-olefins are as described above. From the viewpoint of heat sealability, the density of polypropylene is, for example, 0.88 g / cm 3 More than 0.92g / cm 3 The density is measured in accordance with JIS K7112:1999, Method D (density gradient tube method, 23° C.). From the viewpoint of reducing the environmental load, biomass-derived polypropylene and / or recycled polypropylene may be used. The sealant layer may contain the above-mentioned additives.

[0129] The thickness of the sealant layer is preferably 10 μm or more, more preferably 20 μm or more, and also preferably 200 μm or less, more preferably 150 μm or less, for example, 10 μm or more and 200 μm or less. A laminate having a sealant layer whose thickness is equal to or greater than the lower limit has, for example, excellent seal strength. A laminate having a sealant layer whose thickness is equal to or less than the upper limit has, for example, excellent processability. When a pouch (particularly a retort pouch) is produced from the laminate, the thickness of the sealant layer is preferably 30 μm or more, and also preferably 100 μm or less.

[0130] The sealant film can be produced, for example, by a conventional method. The sealant film can be obtained by mixing the above-mentioned materials by a normal method and forming the resulting mixture into a film by a normal method. The sealant film is preferably a film obtained by extrusion molding. The extrusion molding is preferably performed by a T-die method or an inflation method. Specifically, the material constituting the sealant film is dried as necessary, and then fed to a melt extruder heated to a temperature equal to or higher than the melting point of the material to melt the material, and extruded into a film shape from a die such as a T-die, and the extruded film-like material is rapidly cooled and solidified by a rotating cooling drum or the like, thereby forming a sealant film.

[0131] As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose. The temperature of the molten polymer when extruded from the melt extruder may be, for example, 200°C or more and 300°C or less, or 220°C or more and 270°C or less.

[0132] The composite elastic modulus of the sealant layer is preferably 900 MPa or less, more preferably 830 MPa or less, even more preferably 700 MPa or less, and also preferably 300 MPa or more, more preferably 400 MPa or more, even more preferably 500 MPa or more, for example, 300 MPa or more and 900 MPa or less. A packaging bag produced using a laminate having a sealant layer with a composite elastic modulus within the above range tends to have excellent impact resistance, and therefore excellent bag drop breakage resistance.

[0133] The composite elastic modulus of the sealant layer is measured by a nanoindentation method. Specifically, a nanoindenter is used to measure the composite elastic modulus with the cross section of the sealant layer of the laminate as the measurement surface. The cross section is obtained by cutting the laminate in the thickness direction. The indenter is pressed into the sealant layer near the center in the thickness direction of the sealant layer among the exposed sections of the sealant layer. The measurement conditions are as follows. A Berkovich indenter (triangular pyramid indenter) is used as the indenter of the nanoindenter. The indenter is pressed into the sealant layer from the cross section of the sealant layer to a depth of 100 nm over a period of 3 seconds, held in that state for 5 seconds, and then unloaded over a period of 3 seconds, and the maximum load P max , contact projection area A at maximum depth p A load-displacement curve is obtained. From the load-displacement curve obtained, the composite elastic modulus is calculated according to the following formula (1).

[0134]

number

[0135] The measurement is performed in a room temperature (23°C) environment. The measurement is performed at five or more points on the same cross section, and the composite elastic modulus is recorded as the arithmetic average value of the values ​​measured at five points with good reproducibility. Details of the measurement conditions are described in the Examples section.

[0136] When the sealant layer contains a propylene block copolymer, the composite modulus of elasticity of the sealant layer can be adjusted by the content of ethylene-propylene rubber (EPR). Specifically, the higher the content of ethylene-propylene rubber (EPR), the lower the composite modulus of elasticity can be, and the lower the content of ethylene-propylene rubber (EPR), the higher the composite modulus of elasticity can be. Furthermore, when the sealant layer contains a propylene block copolymer, the composite elastic modulus of the sealant layer can be adjusted by the content of additives such as polyethylene, elastomer, etc. Specifically, the higher the content of the additive, the lower the composite elastic modulus can be, and the lower the content of the additive, the higher the composite elastic modulus can be.

[0137] From the viewpoint of heat sealability, the sealant layer is preferably an unstretched polypropylene film, and the unstretched polypropylene film can be produced by utilizing, for example, a cast method, a T-die method, an inflation method, or the like. The sealant layer may be subjected to the above-mentioned surface treatment.

[0138] [Packaging bag] The laminate of the present disclosure is preferably used as a packaging material. The packaging material is used to produce a packaging bag. The packaging bag of the present disclosure includes the laminate. The laminate of the present disclosure can be used as a packaging material to produce a packaging bag. In one embodiment, the laminate of the present disclosure is folded in half and stacked so that the base material or the first base material is located on the outside and the sealant layer is located on the inside, and the ends or the like are heat-sealed to produce a packaging bag. In another embodiment, a plurality of laminates of the present disclosure are stacked so that the sealant layers face each other, and the ends or the like are heat-sealed to produce a packaging bag. The entire packaging bag may be composed of the laminate, or a part of the packaging bag may be composed of the laminate.

[0139] Examples of packaging bags include packaging bags of various shapes such as standing pouch type, side seal type, two-sided seal type, three-sided seal type, four-sided seal type, envelope seal type, grooving seal type (pillow seal type), pleated seal type, flat bottom seal type, square bottom seal type, gusset type, etc. Examples of heat sealing methods include bar seal, rotary roll seal, belt seal, impulse seal, high frequency seal, and ultrasonic seal.

[0140] The packaging bag may have an easy-to-open portion. Examples of the easy-to-open portion include a notch portion that serves as a starting point for tearing the packaging bag, and a half-cut line formed by laser processing or a cutter as a path for tearing the packaging bag.

[0141] The packaging bag may include a steam release mechanism. The steam release mechanism is configured to communicate between the inside and outside of the packaging bag when the steam pressure inside the packaging bag reaches or exceeds a predetermined value, to release steam, and to suppress steam from escaping at locations other than the steam release mechanism. The steam release mechanism includes, for example, a steam release seal portion protruding from the side seal portion toward the inside of the packaging bag, and a non-seal portion isolated from the content storage portion by the steam release seal portion. The non-seal portion communicates with the outside of the packaging bag. The packaging bag filled with the content and with the opening heat-sealed is heated using a microwave oven or the like. This increases the internal pressure, causing the steam release seal portion to peel off. Steam passes through the peeled portion of the steam release seal portion and the non-seal portion to escape to the outside of the packaging bag.

[0142] The contents to be contained in the packaging bag include, for example, liquids, solids, powders, and gels. The contents may be food or beverages, or non-food or beverages such as chemicals, cosmetics, medicines, metal parts, and electronic parts. After the contents are contained in the packaging bag, the opening of the packaging bag can be heat-sealed to seal the packaging bag.

[0143] As specific examples of packaging bags, a small bag and a standing pouch will be described below. A sachet is a small packaging bag used to hold contents of, for example, 1 g to 200 g. Contents that can be held in a sachet include, for example, sauces, soy sauce, dressings, ketchup, syrups, cooking alcohol, and other liquid or viscous seasonings; liquid soups, powdered soups, fruit juices, spices, pet food, liquid beverages, jelly-like beverages, instant foods, and other foods and beverages; and non-food items such as chemicals, cosmetics, pharmaceuticals, metal parts, and electronic parts.

[0144] The stand-up pouch is used to store contents of, for example, 50 g to 2000 g. Examples of contents that can be stored in the stand-up pouch include shampoo, rinse, conditioner, hand soap, body soap, air freshener, deodorant, insect repellent, detergent, dressing, edible oil, mayonnaise, other liquid or viscous seasonings, liquid beverages, jelly-like beverages, instant foods, other foods and beverages, pet foods, creams, metal parts, and electronic parts.

[0145] In one embodiment, the contents of the packaging bag is pet food.

[0146] In one embodiment, the packaging bag of the present disclosure has excellent gas barrier properties even after heat treatment, and is therefore suitable as a retort-treated pouch (hereinafter also referred to as a "retort pouch") or a boiled pouch (hereinafter also referred to as a "boiled pouch"), or as a microwave-compatible packaging bag. The packaging bag of the present disclosure is also suitable as a boiled or retort pouch for use in a microwave oven. Here, the microwave-compatible packaging bag refers to a packaging bag that can be heated using a microwave oven.

[0147] A retort pouch is a packaging bag that is filled with food or drink, sealed, and then heat sterilized (retort processing) with water or steam at a temperature exceeding 100°C under pressure. A boil pouch is a packaging bag that is filled with food or drink, sealed, and then boiled at a temperature of 100°C or less.

[0148] In one embodiment, the packaging bag of the present disclosure is a retort pouch. There are various conditions for the retort treatment, but any pouch that has undergone general retort treatment is included in the retort pouch. Among the retort treatments, for example, a treatment temperature of 105°C or higher and 115°C or lower may be called semi-retort treatment, a treatment temperature of more than 115°C and 121°C or lower may be called retort treatment, and a treatment temperature of more than 121°C and 140°C or lower may be called high retort treatment.

[0149] In one embodiment, the packaging bag of the present disclosure is a retort pouch. The oxygen permeability (unit: cc / m 2 In one embodiment, the oxygen permeability (day atm) is preferably 2.0 or less, more preferably 1.5 or less, further preferably 1.3 or less, and particularly preferably 1.0 or less. The oxygen permeability is measured in accordance with JIS K7126-2:2006 at a temperature of 23°C and a relative humidity of 90%. The lower limit of the oxygen permeability is preferably as low as possible, but may be, for example, 0.1.

[0150] 7 shows a packaging bag 50 obtained by bonding two laminates together. The shaded areas indicate the heat-sealed areas. The packaging bag 50 may have an easy-to-open part 51. Examples of the easy-to-open part 51 include a notch part 52 that serves as a starting point for tearing, and a half-cut line 53 formed by laser processing or a cutter as a path for tearing.

[0151] FIG. 8 shows a simplified example of the configuration of a standing pouch. The shaded areas indicate the heat-sealed areas. In one embodiment, the standing pouch 60 comprises a body portion (side sheets) 61 and a bottom portion (bottom sheet) 62. The side sheets 61 and the bottom sheet 62 may be made of the same material or different materials. The bottom sheet 62 retains the shape of the side sheets 61, thereby imparting self-supporting properties to the pouch, and the pouch can be made into a standing pouch. A storage space for storing contents is formed within the area surrounded by the side sheets 61 and the bottom sheet 62.

[0152] The standing pouch 60 may include a steam release mechanism 63. The steam release mechanism 63 includes a steam release seal portion 63a protruding from the side seal portion toward the inside of the packaging bag, and a non-sealed portion 63b isolated from the content storage portion by the steam release seal portion 63a. The non-sealed portion 63b communicates with the outside of the packaging bag.

[0153] In the stand-up pouch, only the body portion may be made of the laminate of the present disclosure, only the bottom portion may be made of the laminate, or both the body portion and the bottom portion may be made of the laminate.

[0154] In one embodiment, the side sheet can be formed by making a bag so that the sealant layer of the laminate of the present disclosure is the innermost layer. In one embodiment, the side sheet can be formed by preparing two sheets of the laminate of the present disclosure, overlapping them so that the sealant layers face each other, and heat-sealing the side edges on both sides to make a bag.

[0155] In another embodiment, the side sheet can be formed by preparing two laminates of the present disclosure, overlapping them with the sealant layers facing each other, inserting two laminates folded in a V-shape with the sealant layers facing outward between the laminates at the side edges on both sides of the overlapped laminates, and heat sealing them. According to this production method, a standing pouch having a body with side gussets can be obtained.

[0156] In one embodiment, the bottom sheet can be formed by inserting the laminate between the lower parts of the side sheets that have been made into a bag, and heat sealing the laminate. More specifically, the bottom sheet can be formed by inserting the laminate folded into a V shape with the sealant layer facing outward between the lower parts of the side sheets that have been made into a bag, and heat sealing the laminate.

[0157] In one embodiment, two laminates are prepared, and these are stacked with the sealant layers facing each other. Next, another laminate is folded in a V shape with the sealant layer facing outward, and this is sandwiched under the laminates that have been stacked, and heat sealed to form a bottom. Next, two sides adjacent to the bottom are heat sealed to form a body. In this manner, a standing pouch of one embodiment can be formed.

[0158] [Mechanism of action] Laminates for packaging materials are used to produce packaging bags such as retort pouches. Packaging bags using the laminates are opened after undergoing retort treatment or the like with the contents placed inside. Here, gas barrier properties are required for the packaging bag after retort treatment, so a barrier substrate is used for the laminate. However, if the adhesion between layers is weak in a laminate including a gas barrier substrate and a sealant layer, the packaging bag after retort treatment will lack drop impact resistance. Therefore, it is preferable that the laminate used for the packaging bag maintains the adhesion between layers even after retort treatment.

[0159] If the adhesive layer provided between the layers is made thicker to improve the adhesion between the layers of the laminate, the adhesive may overflow when the laminate is wound up, causing blocking or causing winding slippage due to the lack of initial tack before curing. Therefore, there is a limit to adjustment using only the adhesive layer.

[0160] The laminate of the present disclosure is a laminate of a barrier substrate and a sealant layer via an adhesive layer, and specifies the elastic modulus and thickness of the adhesive layer and the elastic modulus of the sealant layer. The stretched polypropylene substrate constituting the barrier substrate is a stretched substrate having a multilayer structure including at least a first surface resin layer, a polypropylene layer, and a second surface resin layer, and the second surface resin layer having a specific component is disposed so as to face the adhesive layer. As a result, the second surface resin layer and the adhesive layer are firmly bonded, so that the adhesive strength between the barrier substrate and the sealant layer in the laminate is excellent even after retort treatment. Therefore, when the laminate of the present disclosure is used for a packaging bag such as a retort pouch, it has excellent drop impact resistance after retort treatment. In addition, the laminate of the present disclosure has excellent openability after retort treatment because the elastic modulus and thickness of the adhesive layer and the elastic modulus of the sealant layer are specified.

[0161] The present disclosure relates to, for example, the following [1] to

[13] . [1] A laminate having a substrate, an adhesive layer, and a sealant layer in this order in the thickness direction, The substrate is a barrier substrate having a stretched substrate containing polypropylene as a main component and an inorganic oxide layer in this order in a thickness direction, the stretched base material has a multilayer structure including a first surface resin layer, a polypropylene layer, and a second surface resin layer in this order in a thickness direction, and is disposed so that the first surface resin layer faces the inorganic oxide layer and the second surface resin layer faces the adhesive layer; the second surface resin layer contains a random copolymer of propylene and an α-olefin other than propylene in an amount of 50% by mass or more based on the total amount of the second surface resin layer; The adhesive layer has a thickness of 1 μm or more and 4.5 μm or less and an elastic modulus of 20 MPa or more and 50 MPa or less, The sealant layer comprises polypropylene as a main component and has a composite elastic modulus of 900 MPa or less. [2] The laminate according to [1] above, wherein the random copolymer comprises at least one of a propylene-ethylene random copolymer and a propylene-ethylene-butene random copolymer. [3] The laminate according to [1] or [2], wherein the polypropylene layer contains a propylene homopolymer as a main component. [4] The laminate according to any one of the above [1] to [3], wherein the first surface resin layer has the same configuration as the second surface resin layer. [5] The laminate according to any one of the above [1] to [4], wherein the adhesive layer has a modulus of elasticity (MPa) multiplied by a thickness (μm) of 35 or more and 95 or less. [6] The laminate according to any one of [1] to [5], wherein the substrate further comprises a coating layer on a surface of the inorganic oxide layer opposite to a surface facing the stretched substrate. [7] The laminate includes a first substrate, a second substrate, the adhesive layer, and the sealant layer in this order in a thickness direction, the second substrate is the barrier substrate, The laminate according to any one of the above [1] to [6], wherein the stretched base material is disposed so that the first surface resin layer faces the inorganic oxide layer and the second surface resin layer faces the adhesive layer. [8] The laminate according to [7], wherein the first substrate is a stretched substrate containing polypropylene as a main component. [9] A first adhesive layer positioned between the first substrate and the second substrate; a second adhesive layer located between the second substrate and the sealant layer; The second adhesive layer has a thickness of 1 μm or more and 4.5 μm or less and an elastic modulus of 20 MPa or more and 50 MPa or less, The laminate according to [7] or [8], wherein the stretched substrate constituting the second substrate is arranged so that the first surface resin layer faces the inorganic oxide layer and the second surface resin layer faces the second adhesive layer.

[10] The laminate according to any one of [1] to [9] above, wherein the content of polypropylene in the total amount of resin materials contained in the laminate is 80 mass % or more.

[11] The laminate according to

[10] above, which is a packaging material.

[12] A packaging bag comprising the laminate described in

[11] above.

[13] The packaging bag according to

[12] above, which is a pouch that has been retorted or boiled. EXAMPLES

[0162] The laminate and packaging bag of the present disclosure will be specifically described below based on specific examples.

[0163] [Preparation of transparent barrier substrate] ·Transparent barrier substrate 1 A hydroxyl-containing acrylic resin (number average molecular weight: 25,000, glass transition temperature: 99°C, hydroxyl value: 80mgKOH / g) was diluted with a mixed solvent of methyl ethyl ketone and ethyl acetate (mixing ratio 1:1) until the solid content concentration was 10% by mass to prepare a base material. An ethyl acetate solution containing tolylene diisocyanate (solid content 75% by mass) was added to the base material as a curing agent to obtain a solution for forming a surface coating layer. The amount of the curing agent used was 10 parts by mass relative to 100 parts by mass of the base material.

[0164] A biaxially oriented polypropylene film with a thickness of 20 μm was prepared, one side of which was corona-treated. The biaxially oriented polypropylene film was composed of three layers, with a first surface resin layer (first skin layer) of 0.6 μm, a polypropylene layer (core layer) of 18.8 μm, and a second surface resin layer (second skin layer) of 0.6 μm. The ratio of the resin contained in the resin composition constituting the first surface resin layer and the second surface resin layer was 100% by mass of propylene-ethylene-butene random copolymer. The resin composition constituting the polypropylene layer (core layer) contained 100% by mass of homopolypropylene. The above-mentioned solution for forming a surface coat layer was applied to the corona-treated surface (surface of the first surface resin layer) of the film and dried to form a surface coat layer having a thickness of 0.5 μm. In this way, a resin substrate was obtained.

[0165] A carbon-containing silicon oxide (silica) vapor deposition film with a thickness of 12 nm was formed on the surface coating layer of the resin substrate by a roll-to-roll method using a low-temperature plasma chemical vapor deposition apparatus while applying tension to the resin substrate (CVD method). The vapor deposition film formation conditions were as follows:

[0166] (Formation conditions) Hexamethyldisiloxane:oxygen gas:helium=1:10:10 (unit: slm) Cooling / electrode drum power supply: 22kW Line speed: 100m / min

[0167] The carbon percentage C, silicon percentage Si, and oxygen percentage O in the carbon-containing silicon oxide vapor deposition film were measured. The carbon percentage C, silicon percentage Si, and oxygen percentage O were 32.7%, 29.8%, and 37.5%, respectively, based on 100% of the total of the three elements silicon, oxygen, and carbon. The percentages of each element were measured by narrow scan analysis using X-ray photoelectron spectroscopy (XPS) under the measurement conditions described above.

[0168] 385g of water, 67g of isopropyl alcohol, and 9.1g of 0.5N hydrochloric acid were mixed to obtain a solution with a pH of 2.2. 175g of tetraethoxysilane as a metal alkoxide and 9.2g of glycidoxypropyltrimethoxysilane as a silane coupling agent were mixed with this solution while cooling to 10°C to obtain solution A. 14.7g of polyvinyl alcohol with a saponification value of 99% or more and a polymerization degree of 2400 as a water-soluble polymer, 324g of water, and 17g of isopropyl alcohol were mixed to obtain solution B. Solution A and solution B were mixed at a mass ratio (solution A:solution B) of 6.5:3.5 to obtain a barrier coating agent. The barrier coating agent was coated on the deposition film formed on the resin substrate by spin coating, and the mixture was heated in an oven at 80°C for 60 seconds to form a barrier coating layer with a thickness of 300 nm.

[0169] In this manner, a transparent barrier substrate (IBOPP) 1 was obtained which had, in this order, a 20 μm-thick biaxially oriented polypropylene film, a 0.5 μm-thick surface coating layer, a 12 nm-thick carbon-containing silicon oxide (silica) vapor deposition film, and a 300 nm-thick barrier coating layer.

[0170] Transparent barrier substrate 2 Transparent barrier substrate (IBOPP) 2 was obtained in the same manner as the transparent barrier substrate 1 described above, except that the second surface resin layer was a biaxially oriented polypropylene film containing 100 mass% propylene-ethylene random copolymer instead of the 20 μm-thick biaxially oriented polypropylene film (ME-1, manufactured by Mitsui Chemicals Tohcello, Inc.).

[0171] Transparent barrier substrate 3 Transparent barrier substrate (IBOPP) 3 was obtained in the same manner as the transparent barrier substrate 1 described above, except that the second surface resin layer was a biaxially oriented polypropylene film containing 50% by mass of propylene homopolymer and 50% by mass of propylene-ethylene-butene random copolymer instead of the 20 μm-thick biaxially oriented polypropylene film (ME-1, manufactured by Mitsui Chemicals Tohcello, Inc.).

[0172] Transparent barrier substrate 4 Transparent barrier substrate (IBOPP) 4 was obtained in the same manner as the transparent barrier substrate 1 described above, except that the second surface resin layer was a biaxially oriented polypropylene film having a propylene homopolymer content of 70 mass% and a propylene-ethylene-butene random copolymer content of 30 mass% instead of the 20 μm-thick biaxially oriented polypropylene film (ME-1, manufactured by Mitsui Chemicals Tohcello, Inc.).

[0173] Transparent barrier substrate 5 Transparent barrier substrate (IBOPP) 5 was obtained in the same manner as the transparent barrier substrate 1 described above, except that a biaxially oriented polypropylene film not having a second surface resin layer was used instead of the 20 μm-thick biaxially oriented polypropylene film (ME-1, manufactured by Mitsui Chemicals Tohcello Co., Ltd.).

[0174] [glue] The following two-component curing adhesive was used, which is composed of a base agent and a curing agent. Adhesive A Base: Polyester polymer (Mw: 4,000) Hardener: Mixture of HDI and XDI Molar ratio of base agent to hardener (NCO / OH): 2 Adhesive A is substantially free of solvent. Adhesive B Base: Polyester polyurethane polymer (Mw: 30,000) Hardener: A mixture of isophorone diisocyanate (IPDI) trimer and xylylene diisocyanate (XDI) trimethylolpropane (TMP) adduct. Molar ratio of base agent to hardener (NCO / OH): 4 The adhesive B contains a solvent. Adhesive C Base: Polyester polymer (Mw: 30,000) Hardener: A mixture of hexamethylene diisocyanate (HDI) biuret and HDI nurate. Molar ratio of base agent to hardener (NCO / OH): 2 Adhesive C is substantially free of solvent. Adhesive D Base: Polyester polymer (Mw: 3,500) Hardener: Mixture of IPDI and HDI (higher HDI content than IPDI) Molar ratio of base agent to hardener (NCO / OH): 2 Adhesive D is substantially free of solvent.

[0175] [Unstretched polypropylene film] The following was used as the unstretched polypropylene base material (hereinafter referred to as "CPP"). CPP film 1 Unstretched polypropylene film, 60 μm thick, corona-treated on one side (composite modulus: 691.1 MPa) CPP Film 2 Unstretched polypropylene film, 60 μm thick, corona-treated on one side (composite modulus: 902.2 MPa)

[0176] [Example 1] As the first substrate, a biaxially oriented polypropylene film (P2171, manufactured by Toyobo Co., Ltd., hereinafter also referred to as "OPP film") having a thickness of 20 μm and having one surface corona-treated was prepared. As the second substrate, the above-mentioned transparent barrier substrate 1 was prepared. As the sealant layer, a CPP film 1 was prepared.

[0177] A printing layer having a coating thickness of 1 μm (when dried) was formed on the corona-treated surface of the OPP film as the first substrate by the gravure roll coating method. Adhesive A was applied onto the printing layer as the first adhesive layer by the gravure roll coating method, and the adhesive layer surface formed on the first substrate and the barrier coat layer surface of the transparent barrier substrate were bonded together, and aged at 40° C. for 72 hours. Furthermore, a corona treatment was performed on the surface of the second surface resin layer of the transparent barrier substrate 1, and adhesive A was applied as the second adhesive layer by the gravure roll coating method, and the adhesive layer surface formed on the second surface resin layer of the transparent barrier substrate 1 and the corona-treated surface of the CPP film 1 were bonded together, and aged at 40° C. for 72 hours. The thickness of each adhesive layer formed was 2.0 μm.

[0178] In this manner, a laminate was obtained. The obtained laminate had a layer structure of OPP film (20 μm) / printed layer (1 μm) / adhesive layer (2.0 μm) / transparent barrier substrate 1 (21 μm) / adhesive layer (2.0 μm) / CPP film 1 (60 μm). The numbers in parentheses indicate the thickness of each layer. The second surface resin layer constituting the transparent barrier substrate had a propylene-ethylene-butene random copolymer content of 100% by mass.

[0179] [Examples 2 to 4] A laminate was produced in the same manner as in Example 1, except that the type of adhesive and / or the thickness of the second adhesive layer was changed as shown in Table 1. Here, the thickness of the first adhesive layer was also changed in the same manner as the thickness of the second adhesive layer.

[0180] [Examples 5 to 6] A laminate was produced in the same manner as in Example 1, except that the type of the transparent barrier substrate as the second substrate was changed as shown in Table 1.

[0181] [Example 7] A laminate having a two-layer structure was produced in the same manner as in Example 1, except that the first substrate and the first adhesive resin layer were not used.

[0182] [Comparative Example 1] A laminate was produced in the same manner as in Example 1, except that the type of the transparent barrier substrate as the second substrate was changed as shown in Table 1.

[0183] [Comparative Examples 2 to 3] A laminate was produced in the same manner as in Example 1, except that the type of adhesive and / or the thickness of the second adhesive layer was changed as shown in Table 1. Here, the thickness of the first adhesive layer was also changed in the same manner as the thickness of the second adhesive layer.

[0184] [Comparative Examples 4 to 5] A laminate was produced in the same manner as in Example 1, except that the type of adhesive was changed as shown in Table 1.

[0185] [Comparative Example 6] A laminate was produced in the same manner as in Example 1, except that the unstretched polypropylene film as the sealant layer was changed to CPP film 2.

[0186] [Comparative Example 7] A laminate was produced in the same manner as in Example 1, except that the type of the transparent barrier substrate as the second substrate was changed as shown in Table 1.

[0187] [Measurement of elastic modulus] (Elastic modulus of adhesive layer) For the laminate obtained in the above example, a force curve was measured using an atomic force microscope (AFM), and the elastic modulus of the cross section of the adhesive layer was determined from the obtained force curve. The specific measurement procedure is as follows. The laminate obtained in the above example was embedded in an embedding resin to prepare a block, and the block was cut at room temperature (25°C) using a commercially available rotary microtome to prepare a cross section of the laminate. The cross section was obtained by cutting the laminate in the thickness direction perpendicular to the main surface. Finishing was performed with a diamond knife. Using an atomic force microscope (AFM), mapping measurements were performed on the above cross section at a 2.5 μm square including the cross section of the adhesive layer. For the cross section of the adhesive layer, 20 force curves that provided an appropriate force curve shape were selected. Each force curve was fitted according to the JKR (Johnson-Kendall-Roberts) theory to calculate the elastic modulus, and the arithmetic mean value (hereinafter also referred to as the "first arithmetic mean value") of the obtained 20 elastic moduli was calculated. Here, the selected part of the force curve was the vicinity of the center in the thickness direction of the adhesive layer among the parts where the cross section of the adhesive layer was exposed. From the above 20 elastic moduli, three elastic moduli close to the first arithmetic mean value were selected, and the arithmetic mean value (hereinafter also referred to as the "second arithmetic mean value") of the three elastic moduli was calculated. The obtained second arithmetic mean value was taken as the elastic modulus of the cross section of the adhesive layer.

[0188] The details of the AFM measurement conditions are shown below. (AFM elastic modulus measurement) Device name: SPM-9700HT (Shimadzu Corporation) Measurement atmosphere: At room temperature (25℃) Measurement mode: Contact mode Calibration method: Measure the cantilever sensitivity using glass ·Number of measurement points: 64 x 64 points (4096 points in total) Field of view: 2.5μm square Cantilever type: CONTR (manufactured by Nanoworld) Cantilever tip radius: <8nm Cantilever spring constant: 0.2N / m Contact pressure: 0.5V Scan speed: 3Hz Elastic modulus calculation model: JKR (Johnson-Kendall-Roberts) theory Poisson's ratio of sample: 0.4 Analysis software: Nano 3D Mapping (Shimadzu Corporation)

[0189] (Composite elastic modulus of sealant layer) The composite elastic modulus of the sealant layer (Er ) was measured based on the nanoindentation method using a nanoindenter (Bruker's "TI950 TriboIndenter") with the cross section of the sealant layer as the measurement surface. The indenter used for the nanoindenter was a Berkovich indenter (triangular pyramid indenter; Berkovich_TI0039). Measurements were performed at five or more points on the same cross section, and the composite elastic modulus E r The measured values ​​were expressed as the arithmetic mean value of five points that were measured with good repeatability. The number of data points was 200 points / sec.

[0190] The measurement conditions were as follows: a load control method (indentation load 30 μN, loading 3 seconds / holding 5 seconds / unloading 3 seconds). The indenter was pressed into the sealant layer from the cross section of the sealant layer to an indentation load of 30 μN over a period of 3 seconds, and the indentation load was held in this state for 5 seconds. The load was then removed over a period of 3 seconds. This resulted in a maximum load P max , contact projection area A at maximum depth p and a load-displacement curve could be obtained, and the value of the composite elastic modulus was calculated from the obtained load-displacement curve. The measurement was carried out in a room temperature (23°C) environment. The indenter was pressed into the vicinity of the center in the thickness direction of the sealant layer among the portions where the cross section of the sealant layer was exposed. The above cross section was obtained by cutting in the thickness direction perpendicular to the main surface of the laminate. The cross section was prepared by preparing a block in which the laminate was embedded in an embedding resin, and cutting the block using a commercially available rotary microtome in a room temperature (23°C) environment. Finishing was carried out with a diamond knife.

[0191] [Laminate strength] The laminate obtained in the above example was folded in a V shape with the sealant film side facing inward, and heat-sealed to a width of 130 mm and a height of 165 mm to produce a bag-shaped pouch. 100 mL of water was poured into the obtained pouch from the opening, and the opening was heat-sealed to seal it. The sealed pouch was subjected to a retort sterilization treatment using hot water at a retort temperature of 121°C for a retort time of 30 minutes. The laminate after retort sterilization was cut into 15 mm-wide strips extending in the MD direction of the film to obtain test pieces. The laminate strength (N / 15 mm) of the test pieces was measured in accordance with JIS Z1707:2019 using a tensile tester (Tensilon universal material testing machine, manufactured by Orientec Co., Ltd.) at a temperature of 20°C and a relative humidity of 65%, at a peel speed of 50 mm / min and 90° peeling (T-peel method). Specifically, first, a laminate was cut out, and a strip-shaped test piece 100 was prepared by previously peeling the sealant layer side B and the substrate side A by 15 mm in the long side direction. Then, as shown in FIG. 9, the already peeled parts of the sealant layer side B and the substrate side A were gripped by the grips 110 of the measuring device. The grips 110 were pulled at a speed of 50 mm / min in opposite directions perpendicular to the surface direction of the part where the sealant layer side B and the substrate side A are still laminated, and the average value of the tensile stress F in the stable region (see FIG. 10) was measured. The interval S2 between the grips 110 when the pulling started was 30 mm, and the interval S2 between the grips 110 when the pulling ended was 60 mm. FIG. 10 is a schematic diagram showing the change in the tensile stress F with respect to the interval S2 between the grips 110. As shown in Fig. 10, the change in tensile stress F with respect to the spacing S2 passes through a first region R1 and enters a second region R2 where the rate of change is smaller than that of the first region R1. The second region R2 is also called a stable region. The average value of the tensile stress F in the stable region R2 was measured for the five test pieces 100, and the average value was determined as the laminate strength.

[0192] [Seal strength evaluation] The laminate obtained in the above example was folded in a V shape with the sealant film side facing inward, and heat-sealed to a width of 130 mm and a height of 165 mm to produce a bag-shaped pouch. 100 mL of water was poured into the obtained pouch from the opening, and the opening was heat-sealed to seal it. The sealed pouch was subjected to a retort sterilization treatment using hot water at a retort temperature of 121°C for a retort time of 30 minutes. A test piece with a width of 15 mm was cut out perpendicular to the seal portion of the laminate after retort sterilization, and the test piece was attached to a tensile tester (Strograph VG1F, manufactured by Toyo Seiki Seisaku-sho, Ltd.) so that two ends were supported, and the seal strength of the laminate was measured. <Measurement conditions> Tensile test speed: 300mm / min Chuck distance 25mm

[0193] [Impact resistance evaluation] The laminate obtained above was folded in a V shape with the sealant film side facing inward, and heat-sealed to a width of 130 mm and a height of 165 mm to produce 10 pouches. 150 mL of water was filled into the obtained pouch from the opening, and the opening was heat-sealed to seal it. The sealed pouch was dropped 10 times horizontally from a height of 80 cm onto the floor (so that the body of the pouch hits the floor), and then dropped 10 times vertically from a height of 80 cm onto the floor (so that the bottom of the pouch hits the floor), and the number of pouches that broke out of the 10 pouches was counted to evaluate the impact resistance. The results are shown in Tables 1 and 2. <Evaluation criteria> A: No broken bags B: No break in bag, but the seal position has receded C: One or more broken bags

[0194] [Table 1]

[0195] [Table 2] [Explanation of symbols]

[0196] 1: laminate, 10: oriented polypropylene substrate, 20: barrier substrate, 22: oriented polypropylene substrate, 22a: polypropylene layer, 22b: first surface resin layer, 22c: second surface resin layer, 23: surface coating layer, 24: inorganic oxide layer, 25: coating layer, 30: sealant layer, 40, 40A, 40B: adhesive layers, 50: packaging bag, 51: easy-to-open portion, 52: notch portion, 53: half-cut line, 60: standing pouch, 61: body (side sheet), 62: bottom (bottom sheet), 63: steam release mechanism, 63a: steam release seal part, 63b: non-seal part, 100: test piece, 110: gripping tool

Claims

1. A laminate including a substrate, an adhesive layer, and a sealant layer in this order in a thickness direction, The substrate is a barrier substrate having a stretched substrate containing polypropylene as a main component and an inorganic oxide layer in this order in a thickness direction, the stretched substrate has a multilayer structure including a first surface resin layer, a polypropylene layer, and a second surface resin layer in this order in a thickness direction, and is disposed so that the first surface resin layer faces the inorganic oxide layer and the second surface resin layer faces the adhesive layer; the second surface resin layer contains a random copolymer of propylene and an α-olefin other than propylene in an amount of 50% by mass or more based on the total amount of the second surface resin layer; The adhesive layer has a thickness of 1 μm or more and 4.5 μm or less and an elastic modulus of 20 MPa or more and 50 MPa or less, The sealant layer comprises polypropylene as a main component and has a composite elastic modulus of 900 MPa or less.

2. 2. The laminate according to claim 1, wherein the random copolymer comprises at least one of a propylene-ethylene random copolymer and a propylene-ethylene-butene random copolymer.

3. The laminate according to claim 1 , wherein the polypropylene layer contains a propylene homopolymer as a main component.

4. The laminate according to claim 1 , wherein the first surface resin layer has the same configuration as the second surface resin layer.

5. The laminate according to claim 1 , wherein the adhesive layer has a modulus of elasticity (MPa) multiplied by a thickness (μm) of 35 or more and 95 or less.

6. The laminate according to claim 1 , wherein the substrate further comprises a coating layer on a surface of the inorganic oxide layer opposite to a surface facing the stretched substrate.

7. the laminate includes a first substrate, a second substrate, the adhesive layer, and the sealant layer in this order in a thickness direction; the second substrate is the barrier substrate, The laminate according to claim 1 , wherein the stretched base material is disposed such that the first surface resin layer faces the inorganic oxide layer and the second surface resin layer faces the adhesive layer.

8. The laminate according to claim 7 , wherein the first substrate is an oriented substrate containing polypropylene as a major component.

9. a first adhesive layer positioned between the first substrate and the second substrate; a second adhesive layer located between the second substrate and the sealant layer; The second adhesive layer has a thickness of 1 μm or more and 4.5 μm or less and an elastic modulus of 20 MPa or more and 50 MPa or less, The laminate according to claim 7 , wherein the stretched base material constituting the second base material is disposed so that the first surface resin layer faces the inorganic oxide layer and the second surface resin layer faces the second adhesive layer.

10. The laminate according to any one of claims 1 to 9, wherein a content ratio of polypropylene to a total amount of resin materials contained in the laminate is 80 mass% or more.

11. The laminate of claim 10 which is a packaging material.

12. A packaging bag comprising the laminate according to claim 11.

13. The packaging bag according to claim 12, which is a retort or boiled pouch.

Citation Information

Patent Citations

  • Polypropylene multilayered film and composite film

    JP1999334004A

  • Polypropylene laminated film, its manufacturing method and packaging material

    JP2004017615A

  • Film for gas barrier retort pouch

    JP2004050534A

  • Multilayer biaxially oriented polypropylene film

    JP2004345271A

  • Propylenic block copolymer composition and its use

    JP2006124721A